Action research on improving OVP’s service delivery on medicines amidst the pandemic - Zipagan, Jodi B. (Animo Repository, 2020)
This action research explored the available technological advancements which a government institution can tap to improve its service delivery. This was the product of collaboration among several individuals in our organization. While the pandemic has caused a huge disruption among different industries around the world, public service delivery cannot be suspended. Hence, the possibility of tapping a service provider to ease the delay in delivering medicines was considered. Two innovative ways involving the use of digital platform were presented for public value creation. Through this paper, people can have a glimpse of how public service delivery can be better achieved during the pandemic and even moving forward.